2009
DOI: 10.1590/s1807-59322009000200005
|View full text |Cite
|
Sign up to set email alerts
|

Selective Fetoscopic Laser Photocoagulation of Superficial Placental Anastomoses for the Treatment of Severe Twin-Twin Transfusion Syndrome

Abstract: OBJECTIVE: To report our initial institutional experience with fetoscopic laser photocoagulation of placental anastomoses in severe twin-twin transfusion syndrome using a 1.0 mm endoscope. METHODS: Between July 2006 and June 2008, 19 monochorionic diamniotic twin pregnancies complicated by severe TTTS (Quintero stages III and IV) underwent fetoscopic laser therapy. Perinatal data were prospectively collected and compared according to the Quintero stages. RESULTS: Nine patients were classified as stage III and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…By contrast, Ruano et al [11] reported a similar survival rate at 52.6% in both donor and recipient twins. Similarly, in the study of Taylor et al [15] the difference between survival rates of donor and recipient twins did not reach significance.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…By contrast, Ruano et al [11] reported a similar survival rate at 52.6% in both donor and recipient twins. Similarly, in the study of Taylor et al [15] the difference between survival rates of donor and recipient twins did not reach significance.…”
Section: Discussionmentioning
confidence: 94%
“…Apart from these studies performed in experienced centers, there are a few reports from developing countries (table 2). Ruano et al [11] reported an overall survival rate of 52.6% with at least one survivor in 78.9% of cases in Brazil. The corresponding rates were 51.5 and 75.8% in Chile [10] and 60 and 77% in Mexico [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After full-text analysis a total of 34 studies were included in the time-based analysis [10,12,13,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48]. Twelve studies [5,49,50,51,52,53,54,55,56,57,58,59] presented data overlapping other series, of which one presented data relevant for the technique-based analysis [58].…”
Section: Resultsmentioning
confidence: 99%